Diskursus Agama dan Politik dalam Negara Demokrasi: Pemikiran Habermas, Tantangan, dan Etika bagi Indonesia - Zandro, Agrindo; Prasetyo, Matias Rico Adi (Aditya Wacana Pusat Pengkajian Agama Dan Kebudayaan, 2025)
The relationship between religion and politics in Indonesian democracy often generates tension, particularly due to the dominance of majority groups that influence public policy and restrict the freedoms of religious minorities. This article aims to analyze how the thought of Jürgen Habermas can be used to examine and critique the religion–politics relationship within the context of Indonesian democracy. Four core principles of postsecularism—mutual learning, the translation of religious language into secular language, bonum commune, and state neutrality—are employed as the theoretical framework to evaluate non-inclusive democratic practices. This study uses a qualitative approach based on literature review and case analysis, including restrictions on the construction of houses of worship and the politicization of religion during elections. The study shows that Habermas’s ideas can be used to build a political ethics in Indonesia, but they require adaptation to the complex local socio-political realities, including the strong presence of religious identity in the public sphere. Thus, the article concludes that Habermas’s thought is relevant for constructing a more deliberative and inclusive political ethic in Indonesia, and offers a new philosophical approach for criticizing religious exclusivism within majority-rule democracies.